2015
DOI: 10.1097/qai.0000000000000487
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Water, Sanitation, and Hygiene Interventions on the Health and Well-Being of People Living With HIV

Abstract: Although research is required to address behavioral aspects, evidence supports that WASH programming is beneficial for PLHIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 39 publications
3
21
0
1
Order By: Relevance
“…People living with HIV have a higher morbidity where there is contaminated water, poor hygiene and sanitation. Programs to improve these also improved morbidity [93].…”
Section: Disastersmentioning
confidence: 99%
“…People living with HIV have a higher morbidity where there is contaminated water, poor hygiene and sanitation. Programs to improve these also improved morbidity [93].…”
Section: Disastersmentioning
confidence: 99%
“…11,20 In 2015, another study reported the health impact of WASH interventions among PLHIV and concluded that both water quality and handwashing interventions reduced morbidity. 12 It also found that PLHIV residing in households with improved water supplies had less diarrheal morbidity and lower prevalence of intestinal parasites, and that having a household sanitation facility (as compared with open defecation or sharing a facility) reduced the risk of diarrhea. 12 The evidence suggests that improved WASH is important for PLHIV; however, numerous barriers limiting access to these services and facilities have been identified.…”
Section: Introductionmentioning
confidence: 96%
“…12 It also found that PLHIV residing in households with improved water supplies had less diarrheal morbidity and lower prevalence of intestinal parasites, and that having a household sanitation facility (as compared with open defecation or sharing a facility) reduced the risk of diarrhea. 12 The evidence suggests that improved WASH is important for PLHIV; however, numerous barriers limiting access to these services and facilities have been identified. Lack of knowledge, attitudes, cost, and debilitating illness have all been noted as factors that inhibit access to or usage of improved WASH services and facilities by PLHIV.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 Episodes of acute, persistent, and recurrent diarrhea are more likely in HIV-infected children, who are at a greater risk of death from an episode of diarrhea than their immunocompetent peers. 5 Inexpensive interventions, such as household-based water, sanitation, and hygiene (WASH) programs, have been reported to reduce diarrhea and improve overall health in HIV-infected individuals 6,7 and at least 1 study of household water treatment documented decreased diarrhea in HIV-infected children less than 2 years old. 8 …”
Section: Introductionmentioning
confidence: 99%